Self-assembled hole-selective contact for efficient Sn-Pb perovskite solar cells and all-perovskite tandems - Jingwei Zhu; Xiaozhen Huang; Yi Luo; Wenbo Jiao; Yuliang Xu; Juncheng Wang; Zhiyu Gao; Kun Wei; Tianshu Ma; Jiayu You; Jialun Jin; Shenghan Wu; et al. (Nature Communications)
Abstract Self-assembled monolayers (SAMs) have displayed unpredictable potential in efficient perovskite solar cells (PSCs). Yet most of SAMs are largely suitable for pure Pb-based devices, precisely developing promising hole-selective contacts (HSCs) for Sn-based PSCs and exploring the underlying general mechanism are fundamentally desired. Here, based on the prototypical donor-acceptor SAM MPA-BT-BA (BT), oligoether side chains with different length (i.e., methoxy, 2-methoxyethoxy, 2-(2-methoxyethoxy)ethoxy group) were custom-introduced on the benzothiadiazole unit to produce the target SAMs with acronyms MPA-MBT-BA (MBT), MPA-EBT-BA (EBT), and MPA-MEBT-BA (MEBT), respectively, and acting as HSCs for efficient Sn-Pb PSCs and all-perovskite tandems. The introduction of oligoether side chains enables HSCs effectively accelerate hole extraction, regulate the crystal growth and passivate surface defects of Sn-Pb perovskites. In particular, benefiting from the enhanced Sn-Pb perovskite film quality and the suppressed interfacial non-radiative recombination losses, EBT-tailored LBG devices yield a champion efficiency of 23.54%, enabling 28.61% efficient monolithic all-perovskite tandems with an impressive V OC of 2.155 V and excellent operational stability as well as 28.22%-efficiency 4-T tandems.